Consistent annual schedules in a migratory shorebird - Battley, Phil F (The Royal Society, 2006)
Many migratory birds start prebreeding moult and premigratory fuelling some months before the breeding season and face severe time constraints, while travelling up to 15 000 km between non-breeding and breeding grounds. Shorebirds typically leave Southern Hemisphere non-breeding areas over a 3–4 week period, but whether they benefit from interannually consistent timing of departure is unknown. Here, I show that individual bar-tailed godwits (Limosa limosa baueri) from New Zealand are highly consistent in their migratory scheduling. Most birds left within the same week each year (between-year repeatability, r, of 0.83) and adult males, which moult into a bright breeding plumage, were also highly repeatable in the extent of their prebreeding moult (r=0.86). This is consistent with the hypothesis that birds have individually optimized migration schedules. Within adult males, but not females, smaller birds tended to migrate earlier than large birds. Whether this reflects differences in size-related migration speed, optimal breeding time at different sites or size-related natural or sexual selection pressures, remains unknown.